Design and Development of a Wind Turbine Emulator for Analyzing the Performance of Stand-alone Wind Energy Conversion System - M.A. Bhayo; M.J.A. Aziz; N.R.N. Idris; A.H.M. Yatim (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper describes the design and development of a Wind Turbine Emulator (WTE), which can be used to analyze and assess the performance of Wind Energy Conversion System (WECS). The mathematical modeling of the WTE has been done using MATLAB/Simulink platform.  A separately excited DC motor is deployed in order to reproduce the speed/torque, replacing the real wind turbine rotor. The half-bridge DC-DC power converter is developed to run the DC motor in a controlled fashion. Two PI controllers viz speed and current controller are employed which guarantee that the DC motor is following the theoretical (reference) rotational speed of the turbine rotor. A user interface is created in ControlDesk Next Generation, through which the input parameters of the WTE can be altered in real time and the instantaneous effect can be observed by analyzing the output parameters. The designed system offers wide range flexibility and provides a friendly environment in which wind speed and turbine parameters can be altered easily. Hence, offering user to conduct research on variable wind speeds. The DS1104 R&D controller board is employed for implementation of the developed Simulink model. The system design, the model used, and obtained results are presented in this paper.